A DESCRIPTIVE STUDY OF TEACHERS’ REINFORCEMENT IN TEACHING CHILDREN 4-6 YEARS OLD AT CHILDREN’S HOUSE SCHOOL IN ACADEMIC YEAR 2015/2016 - ., Km Adi Nariyana p; ., Prof. Dr.I Nyoman Adi Jaya Putra, MA; ., Ni Komang Arie Suwastini, S.Pd,M.Hum. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Penelitian ini merupakan penelitian deskriptif yang bertujuan menyelidiki 'penguat dalam mengajar anak-anak berusia 4-6 tahun di CH School Jimbaran serta tanggapan siswa terhadap penguatan guru. Subyek penelitian ini adalah guru TK di CH di tahun akademik 2015/2016. Dua kelas yang diambil sebagai sampel yakni Kupu-kupu kecil dan Kupu-kupu. Data penelitian ini dikumpulkan melalui beberapa instrumen; mereka adalah: peneliti, perekam video, kamera dan catatan. Setelah mengumpulkan data melalui observasi dan perekaman video, data dianalisis secara deskriptif. Hasil penelitian ini menunjukkan bahwa guru di Anak Rumah Sekolah menggunakan berbagai macam penguatan positif dan negatif dalam bentuk penguatan verbal dan nonverbal. Penguatan positif yang paling sering disampaikan untuk meningkatkan perilaku positif siswa, adalah penguatan lisan positif seperti yang menyatakan kata-kata positif yang baik, sangat baik, dll guru juga digunakan penguatan negatif dalam proses pembelajaran, baik secara lisan dan non-verbal. Penguatan negatif yang paling sering diterapkan untuk mengurangi perilaku negatif siswa, adalah penguatan lisan negatif. Tanggapan terhadap guru siswa bala yang positif. Ada respon yang diberikan lebih lebih banyak respon positif daripada respon negatif.Kata Kunci : reinforcement, response, positive, negative, verbal, non-verbal This study was a descriptive study aiming at investigating the teachers’ reinforcement in teaching children 4-6 years old at Children’s House School Jimbaran as well as the students’ response to the teachers’ reinforcements. The subjects of this research were preschool teachers in Children House in the academic year 2015/2016. Two classes were taken as samples namely Junior Butterfly and Butterfly class. The data of this research were collected through several instruments; those were: the researcher, video recorder, camera and field note. After collecting the data through observation and video recording, they were analyzed descriptively. The result of this study showed that teachers at Children’s House School used various kinds of positive and negative reinforcement in the form of verbal and nonverbal reinforcement. The most frequent positive reinforcements delivered to increase the students’ positive behaviors, was positive verbal reinforcement such as stating the positive words good, very good, etc. The teachers also used negative reinforcement in the learning process, both verbally and non-verbally. The most frequent negative reinforcement implemented to decrease the students’ negative behaviors, was negative verbal reinforcements. The students’ responses toward the teachers’ reinforcements were positive. There was more positive response from the students than the negative response.keyword : reinforcement, response, positive, negative, verbal, non-verbal